Penguatan Pemahaman Jama’ah Masjid Baiturrahman tentang Bahaya Riba dan Keutamaan Perekonomian Berbasis Syariah: Strengthening Understanding the Congregation of Baiturrahman Mosque Concerning the Dangers of Usury and the Superiority of Sharia-Based Economy - Isti'anah ZA; Ani Yunita; Muhammad Habibi Miftakhul Marwa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
There are still many congregations of the Baiturrahman Mosque who do not understand well about the concept of the prohibition of usury in Islam, so that without realizing it, many of them carry out activities which in the view of Islam are classified as usury because of the lack of understanding of asset management in accordance with sharia principles. Based on the problems faced by the community at the Baiturrahman Mosque as described above, the Service Team needs to provide more understanding to the Baiturrahman mosque congregation about the dangers of usury and the importance of understanding and applying sharia-based economic concepts in everyday life. The activities that will be carried out are conducting intensive studies in the form of material exposure, studies and discussions the dangers of usury and the virtues of sharia economics. The implementation method in the activity includes the preparation stage, the implementation stage and evaluation stage. Based on the pre-test and post-test questionnaire data, participants experienced an increase in understanding of Islamic economic principles in Islamic banking by 18%. Understanding of Islamic financial institutions and conventional financial institutions has increased by 15%. Increased understanding of Interest from banks is Riba by 15.75%. understanding of the dangers of Riba increased by 18.5% and an increase in understanding of islamic financial institution products in accordance with sharia principles by 12.75%.